2003
DOI: 10.1016/s0001-8708(02)00063-4
|View full text |Cite
|
Sign up to set email alerts
|

Euler equations on homogeneous spaces and Virasoro orbits

Abstract: We show that the following three systems related to various hydrodynamical approximations: the Korteweg-de Vries equation, the Camassa-Holm equation, and the Hunter-Saxton equation, have the same symmetry group and similar bihamiltonian structures. It turns out that their configuration space is the Virasoro group and all three dynamical systems can be regarded as equations of the geodesic flow associated to different right-invariant metrics on this group or on appropriate homogeneous spaces. In particular, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
270
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(276 citation statements)
references
References 19 publications
(3 reference statements)
2
270
0
2
Order By: Relevance
“…Its geodesic nature was discovered in [72]. It is also a completely integrable, bihamiltonian equation with an infinite number of conservation laws [61].…”
Section: Geodesic Equationmentioning
confidence: 99%
“…Its geodesic nature was discovered in [72]. It is also a completely integrable, bihamiltonian equation with an infinite number of conservation laws [61].…”
Section: Geodesic Equationmentioning
confidence: 99%
“…It was noted by Constantin & Ivanov [10] that the Hunter-Saxton system allows for peakon solutions; moreover, Lenells & Lechtenfeld [28] showed that it can be interpreted as the Euler equation on the superconformal algebra of contact vector fields on the 1 2-dimensional supercircle, which is in accordance with the by now well-known geometric interpretation of the Hunter-Saxton equation as the geodesic flow of the right-invariantḢ 1 (S) metric on the space of orientationpreserving circle diffeomorphisms modulo rigid rotations [25,[27][28][29] (see also [11-13, 30, 31] for related geodesic flow equations).…”
Section: Introductionmentioning
confidence: 55%
“…A similar approach can be pursued for the general Camassa-Holm equation u t − u txx + 3uu x − 2u x u xx − uu xxx + cu xxx = 0, c ∈ R which can be obtained as the Euler equation for the H 1 right-invariant metric on the Virasoro group [21]. For the Virasoro group, short-time existence of the geodesic flow for the H k metric was established in [9] using the approach given in Section 4.…”
Section: Resultsmentioning
confidence: 99%
“…Other equations from mathematical physics were found to have an interpretation as geodesic flows on diffeomorphism groups (see for example [21,22,31,32]). …”
Section: Introductionmentioning
confidence: 99%